Effects of exponential and conventional fertilization on growth nutrient uptake by five Mediterranean pines in greenhouse - Vila P.; Las Heras J. de; Honrubia M. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
In the present study, we relate seedlings growth parameters (stem thickness and total weight) with nutrient concentrations in five representative pine species of the Iberian Peninsula (Pinus halepensis, P. pinaster, P. pinea, P. nigra, P. sylvestris), fertilized once a week in two ways, with constant doses of nutrients (conventional fertilization) and with increasing amounts of the nutrients (exponential fertilization). All the pines were grown in a transparent glass greenhouse with controlled temperature, luminosity and humidity (using tensiometers inside the pot). Additionally, temperature and soil humidity were measured daily with ten tensiometers (one per pine-substrate combination). The influence of two different growth substrates was investigated with the conventional fertilization regime: a mixture of perlite-vermiculite (1:1 v/v) and coco peat. The exponential fertilization was conducted only in the perlite-vermiculite mixture as substrate. In both fertilizations, the final quantity of nutrients (i.e., the total quantity of nitrogen) supplied to the different pines was the same (70 mg of nitrogen/plant). The experiment was conducted over 32 weeks. Pines specimens were sampled at weeks 12 and 32 (the end of the experiment). There was a generally positive response in the pines fertilized conventionally compared with those fertilized exponentially with respect to all 3 studied parameters. Amongst the different pines species, the mountain pines (P. sylvestris and P. nigra) showed lower values following both fertilizations.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)